2022
DOI: 10.3390/jpm12040563
|View full text |Cite
|
Sign up to set email alerts
|

Small Fibre Peripheral Alterations Following COVID-19 Detected by Corneal Confocal Microscopy

Abstract: A large spectrum of neurological manifestations has been associated with coronavirus disease 2019 (COVID-19), and recently, the involvement of small fibers has been suggested. This study aims to investigate the involvement of small peripheral nervous fibers in recovered COVID-19 patients using in-vivo corneal confocal microscopy (CCM). Patients recovered from COVID-19 and a control group of healthy subjects underwent in-vivo CCM. Corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), corneal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…86 Abnormalities of corneal nerve fibers on confocal microscopy have been reported in patients after COVID-19 compared with controls. 87 Overall, the nature of long COVID and the pathophysiology of the associated neurologic disorders remains uncertain, with limited quantity and quality of evidence. 86 After COVID-19 vaccination, based on Vaccine Safety Datalink data, the US Centers for Disease Control reports a higher risk of GBS with a viral vector vaccine but no increased risk with mRNA vaccines.…”
Section: Key Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…86 Abnormalities of corneal nerve fibers on confocal microscopy have been reported in patients after COVID-19 compared with controls. 87 Overall, the nature of long COVID and the pathophysiology of the associated neurologic disorders remains uncertain, with limited quantity and quality of evidence. 86 After COVID-19 vaccination, based on Vaccine Safety Datalink data, the US Centers for Disease Control reports a higher risk of GBS with a viral vector vaccine but no increased risk with mRNA vaccines.…”
Section: Key Pointsmentioning
confidence: 99%
“…In a retrospective study of 13 patients with post–COVID-19 painful paresthesia, six patients had evidence of small fiber neuropathy on skin biopsy, and two of those six also demonstrated abnormal autonomic testing 86 . Abnormalities of corneal nerve fibers on confocal microscopy have been reported in patients after COVID-19 compared with controls 87 . Overall, the nature of long COVID and the pathophysiology of the associated neurologic disorders remains uncertain, with limited quantity and quality of evidence 86 …”
Section: Viral Infectionsmentioning
confidence: 99%
“…Other studies confirmed and validated the reliability of corneal nerve fiber measurements via ACCMetrics; in particular, the automated quantification of CNFL, CNFD, and CNBD has demonstrated comparable DPN detection ability to manual and semi-automated analysis [ 63 , 130 , 131 ]. Midena et al have recently demonstrated, integrating the ACCMetrics with nerve beading quantification, the presence of corneal neuropathy in subjects previously affected by the COVID-19 disease [ 17 ].…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Our group previously demonstrated how CCM could represent an in vivo, non-invasive, and reproducible diagnostic technique [ 8 ] for the study of corneal morphological alterations not only in diabetic patients but also in other conditions such as post-refractive surgery [ 9 , 10 ], topical chemotherapy in ocular surface squamous neoplasia [ 11 ], vernal keratoconjunctivitis [ 12 ], Wilson disease [ 13 ], oxaliplatin-induced peripheral neuropathy [ 14 ], therapy with epidermal growth factor receptor (EGFR) inhibitor depatuxizumab mafodotin (ABT-414) in patients affected by EGFR-amplified recurrent glioblastoma [ 15 , 16 ], and recently in COVID-19 recovered patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recovered patients have also been affected by small fiber peripheral neuropathy, similarly to other neuronal degenerative diseases, even months after recovery …”
Section: Introductionmentioning
confidence: 99%